2020
DOI: 10.1177/0885066620903027
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hepatic Coagulopathy in Bleeding and Nonbleeding Patients: An Evidence-Based Review

Abstract: Patients with varying degrees of hepatic dysfunction often present with presumed bleeding diathesis based on interpretation of routine measures of coagulation (prothrombin time [PT], international normalized ratio [INR], and activated partial thromboplastin time). However, standard markers of coagulation do not reflect the actual bleeding risk in this population and may lead to inappropriate administration of hemostatic agents and blood products. The concept of “rebalanced hemostasis” explains both the risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…PLT transfusion carries the risk of PLT antibody production, which results in resistance to subsequent PLT transfusion[ 13 ]. Moreover, PLT transfusion still has potential risks[ 14 ], such as infectious diseases caused by blood transfusion, fever, allergic reactions, and hemolytic reactions. Besides, PLT transfusion has a limited effect on CLD, with PLT counts increasing by approximately 10 × 10 9 /L after transfusion[ 15 , 16 ], while PLT transfusion can increase PLT count by 30 × 10 9 /L in healthy patients[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLT transfusion carries the risk of PLT antibody production, which results in resistance to subsequent PLT transfusion[ 13 ]. Moreover, PLT transfusion still has potential risks[ 14 ], such as infectious diseases caused by blood transfusion, fever, allergic reactions, and hemolytic reactions. Besides, PLT transfusion has a limited effect on CLD, with PLT counts increasing by approximately 10 × 10 9 /L after transfusion[ 15 , 16 ], while PLT transfusion can increase PLT count by 30 × 10 9 /L in healthy patients[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Summing up, it can be stated that taking the studies published so far into consideration, a restrictive coagulation management in ESLD patients is warranted as long as patients are not actively bleeding [ 79 ].…”
Section: Timely Management Of Coagulopathy By Using Coagulation Factorsmentioning
confidence: 99%
“…While studies have shown that a progressive decline in liver function does directly correlate to a lower platelet count, there are no formal guidelines for indicators of disease severity [6]. However, since individuals with cirrhosis or chronic liver disease often require frequent interventions or medications, those with severe thrombocytopenia are often associated with poorer prognosis due to delay to treatment [4,7,8].…”
Section: Review Pathophysiology Of Thrombocytopenia In Chronic Liver Diseasementioning
confidence: 99%
“…While it is common practice to monitor platelet levels and intervene prior to planned treatments or procedures, these are not formally indicated but rather more clinician-based [2,8]. Harrison explored further the concept of reliable monitoring, finding no strong evidence towards the predictability of monitoring coagulation tests and bleeding risk; monitoring is often associated with increased prophylactic management in unnecessary cases [7].…”
Section: Review Pathophysiology Of Thrombocytopenia In Chronic Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation